Bio-tensegrity and extracellular matrix disruption in the pathogenesis of persistent post-operative pain: a hypothesis - Plaut, Shiloh (Frontiers in Physiology, 2025)
Persistent post-operative pain (PPOP) is a significant and often debilitating outcome of invasive procedures, with prevalences ranging from 30% to 70% following certain types of surgery. Yet, despite high prevalences and ongoing rigorous research, the pathophysiological mechanisms underlying PPOP remain insufficiently understood. While neurobiological explanations such as nerve injury, peripheral and central sensitization, and neuroma formation have been proposed, theory-based treatments provide only limited relief, resulting in persisting pain and decreased quality of life for affected individuals. This paper presents a framework for the theoretical pathogenesis of PPOP based on a work published recently which offered a connective-tissue-based mechanobioneurological mechanism for the pathophysiology of functional psychosomatic pain syndromes (or “fibromyalgia-type syndromes”), framing fibromyalgia and PPOP as disorders whose mechanism is based in the extracellular matrix’s homeostasis drawing on continuum biomechanics. With its aetiology and mechanisms in dispute, fibromyalgia, which historically was regarded as a connective tissue disorder, has long been a medical mystery. The model offers a mechanistic explanation for ‘primary fibromyalgia syndrome’ as a non-autoimmune disease driven by overactivity of myofascial and interstitial myofibroblasts that sustain mechanical stress within the fascio-musculoskeletal system. Fascia is a hugely overlooked complex delicate viscoelastic and fiber-cellular tissue that extends throughout the human body at various depths and layers and constitutes a complex dynamic interconnected extensive network of connective tissue that undergoes a process of continuous remodeling and transmits and absorbs loads while exhibiting tensegrity-type qualities. Surgical interventions may disrupt biomechanical stability, inducing chronic pain and central neurophysiological aberrations. The model frames these conditions as disorders of interconnected neurobiological and biomechanical systems and opens a new avenue for research on the link between neurobiology and connective tissue.